2007
DOI: 10.1021/ic061990d
|View full text |Cite
|
Sign up to set email alerts
|

Possible Biotransformation Reactions of Polynuclear Pt(II) Complexes

Abstract: The reactions of the two complexes BBR3464 [{trans-PtCl(NH3)2}2{mu-trans-Pt(NH3)2(NH2(CH2)6NH2)2}](4+) and BBR3610 [{trans-PtCl(NH3)2}2{mu-C2H4(NH2(CH2)6NH2)2}](4+) and the corresponding diaqua complexes with the nucleophiles thiourea (tu) and l-methionine (l-Met), were investigated under pseudo-first-order conditions as a function of concentration and temperature, using UV-vis spectrophotometric and stopped-flow techniques. 1H NMR spectroscopy was used to follow the stepwise substitution of the chloro ligands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 38 publications
4
47
0
1
Order By: Relevance
“…Other systematic studies have also been reported by Romeo, van Eldik, Jaganyi, and their respective coworkers [16,20,27,[37][38][39][40][41][42]. These include the investigation into the influence of the bridging ligand on the substitution behavior of dinuclear Pt(II) complexes [37][38][39], the role of cyclometalation in controlling the rates of ligand substitution at platinum(II) complexes [16] and substitution reactions of analogues of cisplatin [40][41][42], and Pt(II) terpy complexes [20,27] with many biologically relevant nitrogen-and sulfur-donors.…”
Section: Introductionmentioning
confidence: 71%
“…Other systematic studies have also been reported by Romeo, van Eldik, Jaganyi, and their respective coworkers [16,20,27,[37][38][39][40][41][42]. These include the investigation into the influence of the bridging ligand on the substitution behavior of dinuclear Pt(II) complexes [37][38][39], the role of cyclometalation in controlling the rates of ligand substitution at platinum(II) complexes [16] and substitution reactions of analogues of cisplatin [40][41][42], and Pt(II) terpy complexes [20,27] with many biologically relevant nitrogen-and sulfur-donors.…”
Section: Introductionmentioning
confidence: 71%
“…However, there is limited information in the literature with regard to the reactivity and thermodynamic properties of the two platinum centers in these types of complexes [38][39][40][41][42][43]. Some data [38,39] suggest that the reactivity and properties of the first platinum center are independent of the state of the second and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Solution of the aqua complex was prepared by suspending a known quantity of the [{PdCl(bipy)}{l-(NH 2 (CH 2 ) 6 H 2 N)}{PtCl (bipy)}]Cl(ClO 4 ) complex in 0.1 M NaClO 4 and adding 3 equivalents of AgClO 4 (with respect to chloride) [28]. The solution was acidified with HClO 4 to pH 2 (for determination of the pK a values).…”
Section: Synthesis Of Complexmentioning
confidence: 99%